2009
DOI: 10.1021/jp8092644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Headgroup Chirality in Nanoassemblies. Part 1. Self-Assembly of d-Isoascorbic Acid Derivatives in Water

Abstract: L-(+)-Ascorbic acid and D-(-)-isoascorbic acid are epimers, with an opposite configuration at the C5 stereogenic chiral center. Single-chained surfactants that carry a L-ascorbic or d-isoascorbic acid residue as hydrophilic headgroup and an alkanoate tail as hydrophobic chain were synthesized. We refer to these as L-ASCn and D-ASCn, with n=8, 10, or 12. The role of the headgroup configuration in determining the nature of both the pure compounds and their nano assembly in aqueous dispersions were studied. Surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(67 citation statements)
references
References 46 publications
5
62
0
Order By: Relevance
“…In part 1, we concluded that the L-ASC headgroups organized in the lamellar packing establish strong intermolecular interactions. 10 The situation is different with the D-ASC heads, due to the weaker intermolecular interactions. In order to investigate the transition detected by DSC measurements at lower temperatures, we repeated the FTIR spectra at 42 and 55°C (see Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In part 1, we concluded that the L-ASC headgroups organized in the lamellar packing establish strong intermolecular interactions. 10 The situation is different with the D-ASC heads, due to the weaker intermolecular interactions. In order to investigate the transition detected by DSC measurements at lower temperatures, we repeated the FTIR spectra at 42 and 55°C (see Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, surfactants that bear chiral headgroups possess peculiar physicochemical properties, depending on the configuration of the stereogenic center, as we have demonstrated in part 1. 10 The presence of two chiral centers, the quite rigid structure of the lactone ring, the presence of several hydroxyl groups that are capable of establishing inter-and intramolecular hydrogen bonding, and the relative flexibility of the hydrophobic side chain, make these molecules a valid tool for investigating the effect of chirality on the physicochemical properties of the supramolecular nanoassemblies they produce.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] More recently, we studied the self-assembly of a bolaamphiphile that carries two L-ascorbic acid moieties, 2 of a double chained derivative, 6 and of D-isoascorbic acid amphiphilic derivatives. 7 We found that changing the stereochemistry from L-ASC to D-isoASC brings about a significant variation in the hydration of the head groups, because of the different set of hydrogen bonding: L-ascorbic acid residues form several intermolecular bonds, while intramolecular interactions prevail in the D-isoascorbic moieties. This stereochemical feature determines different properties in the solid state and in solution.…”
Section: Introductionmentioning
confidence: 82%
“…This result suggests that during the phase transition the dodecyl chains melt almost completely, and that in the gel state the alkyl chains are in a liquid-like state, as in the core of a micellar aggregate. 1 In this simple description we do not disregard the fact that the solvation enthalpy of the ascorbic acid heads is probably lower than that of pure ascorbic acid molecules in water, because the pK a of the hydrophilic heads in the nanostructure is certainly greater than that of L-ascorbic acid in solution (3.36), 7,30 and because water molecules cannot freely interact with the polar heads as they solvate an L-ascorbic acid moiety in a molecular solution. However, the main role in the entire coagel-to-gel transition is certainly played by the aliphatic chains rather than by the head groups.…”
mentioning
confidence: 99%
“…The relationship between the physicochemical properties and the stereochemistry of optically active surfactants derived from bio-based materials, such as sugars 11 , amino acids 12,13 , ascorbic acid 14 , and succinic acid 15 , has been studied by many researchers. Some of them exhibited better surface activities than the corresponding stereochemically mixed surfactants owing to much stronger intermolecular interactions between the surfactant molecules.…”
mentioning
confidence: 99%